PENGARUH FREE CASH FLOW, PERTUMBUHAN PERUSAHAAN, KEBIJAKAN DEVIDEN DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2013 - Ade Dwi Suryani; Muhammad Khafid (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
Debt Policy is policy to decision finance is a policy in determining the company’s funds are sourced from external. Managers must determine the exact proportion of debt with due regard to the risks of the debt. The purpose of this research is to explore how the influence free cash flow, growth of the company, dividend policy and firm size toward the debt policy. Population in this study are all companies listed on the indonesia stock exchange year 2013 obtained 137 company. This research used purposive sampling method. The analysis show that they have one variable is dividend policy has positive influence to debt policy. As for the other three variables independent are free cash flow, growth of the company, and firm size that insignificant influence to debt policy. The conclusions of this study proved that the dividend policy can improve the company’s debt policy. Suggestion for future research to use an independent commissioner and the implementation of good corporate governance to supervise the activities of the company and improve its performance. Keywords: Free cash flow, debt policy, dividend policy, firm size, growth of the company